BIOMECHANICAL COMPARISON OF LOCKED PLATING AND SPIRAL BLADE RETROGRADE NAILING OF SUPRACONDYLAR FEMUR FRACTURES - Assari, Soroush (Temple University Libraries, 2011)
Mechanical Engineering === M.S.M.E. === Background: Comminuted supracondylar femur fractures in the elderly are often treated with either retrograde femoral nailing or locked plating. Early weight-bearing is typically restricted after fixing supracondylar fractures, thereby impairing the patient's mobilization. In general, surgeons are more comfortable allowing early weight-bearing of long bone fractures after nailing rather than plating, but early studies of retrograde nails for supracondylar fractures using standard distal locking showed poor fixation compared with locked plating. Newer generation distal locking techniques, such as the spiral blade, may demonstrate improved fixation, potentially allowing early weight bearing. The purpose of this study is to biomechanically compare locked plating with retrograde nailing of osteoporotic supracondylar femur fractures with simulated physiologic weight-bearing in the post-operative period. Methods: The Locking Condylar Plate (LCP) and Retrograde/Antegrade EX Femoral Nail (RAFN) with spiral blade locking were tested using 10 paired elderly cadaveric femurs, divided into normal and low BMD groups, with a simulated AO/OTA type 33-A3 supracondylar femur fracture. Each specimen was subjected to 200,000 loading cycles simulating six weeks of postoperative recovery with full weight-bearing for an average individual and the construct subsidence and axial stiffness were measured. Results: LCP fixation compared to RAFN showed higher axial stiffness for normal and low BMD groups (80% and 57% respectively). After cyclic loading, axial stiffness of both constructs decreased by 20% and RAFN fixation resulted in twice as much subsidence (1.9±0.6 mm). Two RAFN constructs with low BMD failed after a few cycles whereas the matched pairs fixed with LCP failed after 68,000 and 100,000 cycles. Conclusions: The LCP construct was stiffer than RAFN construct. Early weight bearing may cause 3-4 mm of subsidence in elderly patients with low BMD. However, because of the observed failures in two of the samples treated with RAFN in the low BMD group, early weight bearing is not recommended in osteoporotic bones treated with RAFN. === Temple University--Theses